AGGRESSIVENESS AND HOST SPECIFICITY OF TOMATO AND POTATO ISOLATES OF PHYTOPHTHORA INFESTANS - Sharma, Sanjeev (Potato Journal, 2016)
Late blight, caused by the oomycete Phytophthora infestans, is one of the most severe threats to potato and tomato production worldwide, including India. To know the differences in aggressiveness and host specificity between potato and tomato P. infestans population, isolates were collected and cross inoculated. No significant effects of isolate, host or host x isolate interaction were found. All isolates produced symptoms on both the hosts and irrespective of the origin of the isolates; larger lesions were produced on potato than tomato. Similarly higher lesion expansion rate values were recorded on potato than tomato. Spore production varied depending upon the host-isolate combination and higher values were estimated when isolates were inoculated on their original hosts. No significant differences were observed for aggressiveness thereby indicating that there is no host specificity to tomato or potato within P. infestans population.